Abandon the Dark - Perry, Marta (Thorndike, Maine : Center Point Large Print, 2015)
"Lainey Colton returns to Deer Creek, Pennsylvania, to care for her beloved great-aunt Rebecca. Lawyer Jake Evans questions her motives, but is drawn to her. However, no amount of attraction will matter if he can't keep her safe from a mysterious threat"--
Keywords: Large type books; Romantic suspense fiction